Gerald's Emotional State in The Last Wish - Agustiana, Vina; Rahmatunisa, Wulan; Nuruliya, Shifa (Jurnal Pendidikan Bahasa dan Sastra, 2023)
Psychology is a general concept that every human being possesses. Using Freud's Psychoanalytic Theory, this study investigates the types of Psychological Aspects found in Geralt, the main character in Andrzej Sapkowski's novel "The Witcher: The Last Wish" (Id, Ego, and Superego). The researcher used the qualitative method and a case study design to achieve the research goal. The data is gathered through document analysis in the form of the main character's utterances. The researcher discovered 806 data from Geralt's utterances, with 149 data (18.48%) included the Psychological Aspects. According to the findings, 34 data were assigned to the Id (22.81%), 40 data were assigned to the Ego (26.84%), and 75 data were assigned to the Superego (50.33%). The most noticeable Psychological Aspect of Geralt's character is Superego. The superego is the component of personality acquired from one's parents, and society includes the values and morals of society learned from one's parents and others. According to the story, Geralt has been an orphan since he was a child and has survived to grow up on his own.